2019
DOI: 10.1111/ggi.13819
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of violence against older adults and associated factors in Çanakkale, Turkey: A cross‐sectional study

Abstract: AimThis study was designed to determine the prevalence of domestic violence against older adults and the associated risk factors in Çanakkale, Turkey.MethodsA cross‐sectional, population‐based study was carried out, including 1230 individuals aged ≥65 years living in the city of Çanakkale, Turkey. The population of the study consisted of 73 367 individuals aged ≥65 years, living in Çanakkale. Sample selection was made with the one‐step cluster sampling method. The data were collected by face‐to‐face interview.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Higher educational attainment may affect the level of openness on abuse among the older adults and therefore they may be unwilling to share information on sensitive topics like abuse to maintain a family façade [8]. A popular believe is that, those who are economically independent have lesser odds of experiencing violence [38]. However, our results indicated otherwise -older adults with working status experience higher odds of violence.…”
Section: Discussionmentioning
confidence: 65%
“…Higher educational attainment may affect the level of openness on abuse among the older adults and therefore they may be unwilling to share information on sensitive topics like abuse to maintain a family façade [8]. A popular believe is that, those who are economically independent have lesser odds of experiencing violence [38]. However, our results indicated otherwise -older adults with working status experience higher odds of violence.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast to these studies, another study also states that compared to women who attended fewer years of schools, those who attended more years of school are just more likely to report economic violence [25]. The partner's level of education is also effective on economic violence [49]. Educational differences between of the woman and her husband/partner are also significantly associated with economic abuse [38].…”
Section: Literature Reviewmentioning
confidence: 94%
“…It was found in a study conducted in Konya, that 13.5% of married women were exposed to sexual and economic violence [14]; in another study conducted in Turkey's capital Ankara showed that 60.4% of women [28] and 19.3% of the women in Edirne, were exposed to economic violence [47]. In a study conducted with women admitted to the IVF Center in southwest Turkey, 19% of the participants [48] and, in another study conducted with individuals aged 65 and over living in Ç anakkale, it was found that 12.2% of the participants were exposed to economic violence [49].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations